2021
DOI: 10.3389/fphar.2021.778613
|View full text |Cite
|
Sign up to set email alerts
|

Large Amino Acid Mimicking Selenium-Doped Carbon Quantum Dots for Multi-Target Therapy of Alzheimer’s Disease

Abstract: Multi-target intervention and synergistic treatment are critical for the drug development of Alzheimer’s disease (AD) due to its complex and multifactional nature. Oxidative stress and amyloid β peptides (Aβ) accumulation have been recognized as therapeutic targets for AD. Herein, with ability to inhibit Aβ aggregation and the broad-spectrum antioxidant properties, the large amino acid mimicking selenium-doped carbon quantum dots (SeCQDs) are presented as novel nanoagents for multi-target therapy of AD. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Inhibiting Aβ aggregation and Scavenging the ROS [221] Se-CQDs Anti-oxidation Scavenging the ROS [222] gCDs-E Hydrophobic interactions/anti-oxidation Suppressing fibrillation/ Disaggregation/Inhibition fungi [13] bPEI@CDs Electrostatic interactions/ photooxygenation Inhibition/Disaggregation [231] OPCDs Chelation/hydrophobic interactions/ photooxygenation Inhibition [232] Apta@CDs Photooxygenation/target Inhibition [229] CPDs Electrostatic interactions/hydrogen bonds/hydrophobic interactions Inhibition/Disaggregation [233] C 60 Hydrophobic interactions Inhibition [234] UCNP@C 60 -pep Photooxygenation/anti-oxidation Inhibition/scavenging the ROS [236] 4 Others…”
Section: Gqdsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibiting Aβ aggregation and Scavenging the ROS [221] Se-CQDs Anti-oxidation Scavenging the ROS [222] gCDs-E Hydrophobic interactions/anti-oxidation Suppressing fibrillation/ Disaggregation/Inhibition fungi [13] bPEI@CDs Electrostatic interactions/ photooxygenation Inhibition/Disaggregation [231] OPCDs Chelation/hydrophobic interactions/ photooxygenation Inhibition [232] Apta@CDs Photooxygenation/target Inhibition [229] CPDs Electrostatic interactions/hydrogen bonds/hydrophobic interactions Inhibition/Disaggregation [233] C 60 Hydrophobic interactions Inhibition [234] UCNP@C 60 -pep Photooxygenation/anti-oxidation Inhibition/scavenging the ROS [236] 4 Others…”
Section: Gqdsmentioning
confidence: 99%
“…This study contributed to understanding the pathological link between bacterial metabolites and amyloid diseases. Due to the excellent antioxidant capacity of selenium nanoparticles, Zhou et al 221 designed selenium-doped carbon quantum dots (Se-CQDs) via a simple hydrothermal treatment of selenocystine, which were successfully applied to inhibit Aβ aggregation and scavenge the redundant ROS in the brain ( Fig. 13B ).…”
Section: Zero-dimensional Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanozyme usually refers to artificial enzymes which present highly effective enzyme-like properties and could be widely used for anti-inflammatory, anti-oxidative damage and cancer treatments, etc. [23][24][25][26][27][28][29]. In recent years, studies have shown that cerium oxide nanoparticles (CNPs) present good antioxidant capacity and the ability to scavenge excess reactive oxygen species [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, small-sized carbon dots can penetrate various biological barriers in the body providing therapeutic effects. 93,94 In addition to conventional imaging agents, CDs have developed many new applications as nanozymes in recent years, such as antibacterial mouthwash. 95 The various properties of CDs make promising for multi-functional diagnosis and treatment applications.…”
mentioning
confidence: 99%